The Development of E-Book Based on Modified Free Inquiry on Ecology Topic to Train Critical Thinking Skills in Class X High School Students - Fitry Larassati; Fida Rachmadiarti (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2021)
The development of information and communication technology (ICT) which intensively provides convenience and practicality in implementing learning activities, especially during this pandemic, which requires learning to be done online. However, this does not prevent students from having critical thinking skills in the 21st century. Students' critical thinking skills can be trained using a modified free inquiry model because students are required to independently find answers to existing problems. Modified free inquiry model is the collaboration or modification of both the guided inquiry and the free inquiry model. Therefore, the use of technology is very necessary to prepare teaching materials that can train critical thinking skills. The purpose of this research was to develop e-book based on modified free inquiry on ecology topic to train critical thinking skills that are valid theoretically and empirically. This research used 4D development model (Define, Design, Develop, and Disseminate), without a dissemination stage. The e-book developed was tried out limited on 10 students of SMAN 19 Surabaya grade 10th. The validity of the e-book is determined from the validation results of experts (education experts and material experts) and biology teachers in terms of presentation, content, and language components. The practicality of the e-book is determined by student responses. The data analysis technique was carried out by descriptive quantitative. The results of the validity analysis showed an average percentage of 93.93% with a very valid category, while the results of the student responses obtained an average percentage of 98.88% with a very feasible category. Thus, it can be concluded that the modified free inquiry e-book on ecology topic to train critical thinking skills in class X high school students could be used in biology learning. Keyword: E-book, modified free inquiry, Critical thinking, Ecology